Dualisme Kebijakan Keamanan Nuklir Korea Utara Melalui Uji Coba Rudal Antar Benua Tahun 2021-2022 - Alunaza, Hardi; Ernianda, Annisa; Ilmah, Daris Nurul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
In 2021-2022, North Korea's nuclear developments surprised public. The testing of missiles over the past year produced the latest advanced nuclear. North Korea developing new an intercontinental nuke called